Pengaruh Karakteristik Komite Audit terhadap Internet Financial Reporting pada Bank Umum Swasta di Indonesia - Elisabeth Lusi Tania; Bernadetta Laras Mei Daningtyas; Aloisius Irgi Sheridandi; Imelda Sinaga (Program Studi Akuntansi Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar, 2023)
Internet Financial Reporting (IFR) is one of the implementations of internet financial reporting on a company website. The existence of IFR can help a company in conveying both financial and non-financial information widely. During the Covid-19 pandemic, it required companies to need internet access in carrying out their activities, both financial and non-financial information. For the context of publication and transparency of financial statments, a complete disclosure process is required. The study aims to examine the size of the audit committee, the financial expertise of the audit committee, and the frequency of audit committee meetings on Internet Financial Reporting. The population used is private commercial banks in Indonesia that are registered with the Financial Services Authority. The data used in this study are annual reports for three consecutive periods and information from each bank through the website of each bank to reveal the IFR index. The research method used descriptive statistical analysis and a logistic regression test was carried out. Based on the research results, it can be concluded that the size of the audit committee and the frequency of audit committee meetings do not affect Internet Financial Reporting. Meanwhile, the audit committee's financial expertise influences Internet Financial Reporting.